Technical feasibility and clinical success of direct “free hand” EUS-guided gastroenterostomy in patients with gastric outlet obstruction - Fischer, Hanna; Rüther, Katharina; Abdelhafez, Mohamed; Götzberger, Manuela; Dollhopf, Markus; Schlag, Christoph (Endoscopy International Open, 2022)
Background and study aims Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) with lumen-apposing metal stents (LAMS) appears to be a promising intervention in management of gastroduodenal out obstruction (GOO), particularly for patients for whom surgery is high risk or in a palliative setting. This study aimed to evaluate the technical feasibility, procedure-associated adverse events (AEs), and clinical outcome of direct “free hand” EUS-GE.Patients and methods This retrospective two-center study included patients who underwent direct “free hand” EUS-GE (April 2017 to March 2021) investigating technical success (correctly placed LAMS), clinical outcome (successful oral nutrition), and management of procedure-associated AEs. “Free hand” was defined as the use of the electrocautery enhanced stent delivery system alone without additional guidewire-assistance for EUS-GE creation.Results Forty-five patients (58 % women/42 % men; mean age 65 years) with malignant (n = 39), benign (n = 4) or unclear (n = 2) GOO underwent direct “free hand” EUS-GE. The technical success rate was 98 % (44/45). Of the patients, 95% (42/44) had less vomiting and increased ability to tolerate oral food intake after the intervention. In one patient, a second EUS-GE was necessary to achieve sufficient clinical improvement. Procedure-associated AEs were observed in 24 % (11/45) of cases including stent misplacement (n = 7), leakage (n = 1), development of a gastrojejunocolic fistula (n = 1), and bleeding (n = 2), which could be all managed endoscopically.Conclusions Direct EUS-GE has a favorable risk-benefit profile for patients with GOO, showing high technical success rates, manageable AEs, and rapid symptom relief.